The paradigm of conversion in Luke - Méndez-Moratalla, Fernando (Journal for the study of the New Testament. Supplement series ;, 2004)
Conversion is a main theological theme in the Lukan corpus. Since much attention has been paid to the issue in Acts, the present work shows how the evangelist also conveys his theological emphasis on conversion in his gospel through material either unique to it or that Luke has edited to this purpose. Attention is paid to the different issues involved in LukeGÇÖs emphasis on conversion and an attempt is made to place them within the larger spectrum of his theology. The grouping of all these elements provides the basis for constructing LukeGÇÖs paradigm of conversion.